The candy shop war - Mull, Brandon, 1974- (Mull, Brandon, 1974- Candy shop war, 2014)
When fifth-graders Nate, Summer, Trevor, and Pigeon meet the owner of the new candy store in town and are given a magical candy that endows them with super powers, they find that along with its benefits there are also dangerous consequences.